Pengaruh Penerapan Model Pembelajaran Creative Problem Solving Terhadap Kemampuan Pemecahan Masalah Matematis Peserta Didik Kelas IX SMPN 1 2x11 Kayutanam - SYARIANTI . (Jurnal Edukasi dan Penelitian Matematika, 2019)
Based on the results of daily mathematic test of class IX SMPN 1 2x11 Kayutanam, it was found that the student’s mathematical problem solving abilities were not optimal. It has to be surmounted to achieve the objectives of learning mathematics. One of other solution that appropiate this problem is to use the creative problem solving learning model. The purpose of the study was to describe wheter the student’s problem solving ability class IX SMPN 1 2x11 Kayutanam who use creative problem solving learning model is better than those using the direct learning model. Based on the results of the final test mathematical problem solving ability, it was founded that  an average value of the final test of the experimental class is better than the final tea value of the control class. It can be concluded that the mathematical problem solving ability of students who learn using the creative problem solving learning model is better than students who use the direct learning model.Keywords--Mathematical Problem Solving Ability, Direct Learning Model, Creative Problem Solving Learning Model.